2021
DOI: 10.1192/bjo.2021.982
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns in psychiatric compulsory care: polypharmacy and high-dose antipsychotics

Abstract: Background Antipsychotic polypharmacy and prescription of high-dose antipsychotics are often used for the treatment of psychotic symptoms, especially in compulsory psychiatric care although there is lack of evidence to support this practice and related risks for patients. Aims We aimed to investigate prescription patterns in patients with psychosis under compulsory psychiatric treatment in Cyprus and to identify predictors for pharmaceutic treatment patterns. Method Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In this study, the QI values decreased with the inclusion of PRN prescriptions for all QIs except no prescription ratio of mood stabilizers and antiepileptics. A previous study suggested that the polypharmacy ratio increases when PRN prescriptions are included [ 36 ], and a similar trend might be observed in this study. Furthermore, a positive correlation was found between QI values for regular prescriptions and the QI ratio for both schizophrenia and MDD.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the QI values decreased with the inclusion of PRN prescriptions for all QIs except no prescription ratio of mood stabilizers and antiepileptics. A previous study suggested that the polypharmacy ratio increases when PRN prescriptions are included [ 36 ], and a similar trend might be observed in this study. Furthermore, a positive correlation was found between QI values for regular prescriptions and the QI ratio for both schizophrenia and MDD.…”
Section: Discussionsupporting
confidence: 90%
“…Another study in a Canadian psychiatric intensive care unit revealed one quarter of patients' PRN antipsychotic orders exceeded the recommended maximum dose in a day (Casol et al, 2021). High use of PRN medication in acute mental healthcare settings was linked to polypharmacy problems (Kaikoushi et al, 2021; Martin et al, 2017). However, polypharmacy is expected among patients with severe mental symptoms and/or limited response to medication treatments (Kaikoushi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…High use of PRN medication in acute mental healthcare settings was linked to polypharmacy problems (Kaikoushi et al, 2021; Martin et al, 2017). However, polypharmacy is expected among patients with severe mental symptoms and/or limited response to medication treatments (Kaikoushi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Other studies showed a link between prolonged experience of mental health problems, including psychotic symptoms, and advanced therapeutic schemas in terms of high doses of antipsychotics. 25 One way to interpret the present association between cognitive impairment, general psychotic symptoms and prescription of high doses of antipsychotics is that high-dose antipsychotics and cognitive impairment are attributable to the severity of the underlining disease. Indeed, there is evidence that cognitive decline in psychosis starts at least a decade before the onset of psychotic symptoms, and this is more profound in individuals with schizophrenia, who experience a decrease in IQ at a rate of 0.35 points per year.…”
Section: Discussionmentioning
confidence: 99%